Computational crashworthy optimization of partially filled aluminium foam for automative side member - Salwani, Mohd Salleh (2013)
Lightweight design with good crashworthy characteristic is highly desirable in automotive industry. Frontal crashes is identified as the most often occurrence. Frontal collision occurred at an angle up to 30 degree, so called oblique, as prescribed in Federal Motor Vehicle Safety Standard is used in this study. Geometry changes and material replacement is approaches used to improve the crash performances. Simulation is carried out using Ls-dyna software and optimization is done by using Sequential Quadratic Programming that is run in Matlab. The structure in this study is using aluminum and aluminum foam. The structure is partially filled to reduce the additional weight cause by the foam. Furthermore, the column thickness, foam length and foam density is varied to achieve the target.From the analysis of partially filled column, it was found that crush force efficiency (CFE) is highly affected by the loading angle unlike specific energy absorption (SEA). The initial response is however ruled by thin-walled aluminum deformation behavior. Introduction of partially filled column promotes improvement in SEA and CFE. SEA of the new design and empty column is 1237.76 J/kg and 907.28 J/kg with CFE of 0.7 and 0.5, respectively.A surrogate based optimization program developed by employing the Sequential Quadratic Programming method yield an optimum design of(t, L)* = (2.3,15 1.7) and (t, L)* = (1.1,199), for SEA and CFE, respectively. In three variables optimization, the optimum design for maximum SEA and CFE are (t, L, p)* = (2.0,88.6,0.1) and (t ,L,p)* ( 1.4, 129.6, 0.2). In term of occupant safety, car associated with partially filled side member exhibit lowest index in occupant injury criteria, 496.6, 694 and 850 for HIC15, H1C36 and CSI, respectively. The results show that the crashworthiness performance of the structure can be improved through introduction of partially filled column. Using the developed programming for optimization, vehicle structures design can be practically optimized.